Polygamy, policy and postcolonialism in English marriage law : a critical feminist analysis - Naqvi, Zainab Batul (Law, society, policy series., 2023)
Using a critical postcolonial feminist lens, this book provides a contextualised exploration of English legal responses to polygamy.